Photodynamic Therapy with the Silicon Phthalocyanine Pc 4 Induces Apoptosis in Mycosis Fungoides and Sezary Syndrome - Minh Lam; YooJin Lee; Min Deng; Andrew H. Hsia; Kelly A. Morrissey; Chunlin Yan; Kashif Azzizudin; Nancy L. Oleinick; Thomas S. McCormick; Kevin D. Cooper; Elma D. Baron (Advances in Hematology)
Our current focus on the effects of Photodynamic Therapy (PDT) using silicon phthalocyanine Pc 4 photosensitizer on malignant T lymphocytes arose due to preclinical observations that Jurkat cells, common surrogate for human T cell lymphoma, were more sensitive to Pc 4-PDT-induced killing than epidermoid carcinoma A431 cells. Mycosis fungoides (MF) as well as Sezary syndrome (SS) are variants of cutaneous T-cell lymphoma (CTCL) in which malignant T-cells invade the epidermis. In this study, we investigated the cytotoxicity of Pc 4-PDT in peripheral blood cells obtained from patients with SS and in skin biopsies of patients with MF. Our data suggest that Pc 4-PDT preferentially induces apoptosis of CD4+CD7− malignant T-lymphocytes in the blood relative to CD11b+ monocytes and nonmalignant T-cells. In vivo Pc 4-PDT of MF skin also photodamages the antiapoptotic protein Bcl-2.